Penggunaan Operkulum dalam Penentuan Umur pada Rhinoclavis sinensis Gmelin 1791 (Gastropoda: Cerithiidae) - Zahida, Felicia; Subagja, Jusup (Universitas Atma Jaya Yogyakarta, 2010)
Age determination of the sample specimen is very important for population dynamic research of R. sinensis (Gastropoda : Cerithiidae). Operculum is a â€œhardâ€ part stick on the dorsal portion of the foot of gastropods. Operculum appeared on the day of the snails are born and have their own specific shape, size, and materials composition. The aim of this research was to describe the use of operculum in age determination of R. sinensis. The method used in this research was: the operculums were soaked into saturated sodium hydroxide, washed and mounted them in Canada balsam, and observed using binocular microscope. Regression analysis was used to find the relationship between length of operculum to length of shell, and number of adventicious layers of operculum to length of shell. The research resulted that the length of operculum was comparable with the shell length, with the regression line of Y=0.113X +1.898 (R2=0.857). The growth of adventitiousâ€™ layers of the operculum coincided with the growth of the shell that in the second year, the growth of adventitious layers was two layers a year. At the age of three and four, the growth was one layer a year. During the fifth, sixth and seventh years, the growth was only a layer within three years. The regression line was Y=0.168X (R2=0.872).